IDEOLOGI DAN AKTIVITAS POLITIK BUYA HAMKA DALAM NOVEL HAMKA: SEBUAH NOVEL BIOGRAFI KARANGAN HAIDAR MUSYAFA - Dian Ismi Islami; Reygi Prabowo (Jurnal Pustaka Komunikasi, 2019)
The purpose of the research is to describe the ideology and political activities of Buya Hamka. In this study, researchers used qualitative research methods and critical analysis. The theory used in this study is Teun A. Van Dijks Critical Discourse Analysis. The paradigm of this research is critical. The qualitative research approach, the type and format of descriptive research, is the object of research in the novel HAMKA: A Novel Biography written by Haidar Musyafa while the research subjects are Ideology and Political Activities which are discussed in the book. Data collection techniques carry out critical linguistic methods, in-depth interviews, and literature studies, data analysis techniques using source triangulation. The results of the study show that the novel HAMKA: A Novel Biography written by Haidar Musyafa discusses Hamkas ideology, pan-Islamism. But Hamkas dialectical process towards his ideology, the interesting process of Hamkas ideology, such as Hamkas intersection with communism, even to the point where he had sung communist marches like the International with his friends in Java, was not described in the novel.